Governance Strategies for the Management of Museums and Heritage Institutions - Héctor Moreno Mendoza; Agustín Santana Talavera (Heritage)
The management of museums and cultural heritage institutions requires a collaborative approach that involves diverse actors in decision-making. This study analyses four models of cultural management (dependent, autonomous, non-profit, and private) through case studies on the island of Gran Canaria, highlighting their advantages and limitations. As a result, a hybrid model of governance is proposed that integrates elements of the public, private, and social sectors, promoting the active participation of all stakeholders. However, the implementation of this model faces challenges such as resistance to change on the part of some institutions, the difficulty of coordinating divergent interests between public and private actors, and the need to establish regulatory frameworks that facilitate collaboration without compromising heritage conservation. Despite these obstacles, this approach seeks to improve the sustainability, efficiency, and adaptability of heritage institutions to contemporary tourism and conservation challenges.